The Relationship between Internet Usage and the Marketing of Tourism in Libya - Elkwash, Ahmed M. Omar (2009)
Since the Internet has been shown in recent literature to be a pervasive system in tourism it is important to understand its roles in more detail. The basis for this study regarding to the Internet is an important information source for participants in tourism and, as such, figures prominently in various tourism decision-making processes. From this, the goal in order to develop e-tourism, stakeholders have to examine the use of the Internet as a marketing tool in tourism in Tripoli of Libya. In addition to the importance of attitudes toward the behavior in question, some of these studies have found subjective norms to also be important, while others have found perceived behavioral control to also be important. This study demonstrates the increased power of the TPB over the simple TRA. As more and more studies of Internet purchasing behavior and its antecedents are done within the TPB framework, we are more able to discover and confirm which antecedents are most important, helping us build a robust theory of Internet behavior. From a practical perspective, as a cumulative body of work on Internet purchasing emerges, it will be better able to advise vendors on the elements they need to address in order to increase their Web site traffic. In this study, the one area of findings that may help Web merchants the most concerns trust. It has been found that beliefs about the trustworthiness of the Internet as a channel for conducting personal business were associated with positive attitudes toward Internet purchasing, and these positive attitudes were in turn associated with actual purchasing behavior on e-Tourism.